Digital Transformation in Banking Services: A Literature Review on Customer Behavior Shifts and Fintech Innovations - Fatmasari, Raden Roro (Yayasan Kreatif Indonesia Emas, 2024)
The global banking industry is undergoing a profound digital transformation, primarily driven by rapid technological advancements and the disruptive influence of financial technology (fintech) firms. This paper presents a systematic literature review to synthesize key findings on this transformation, focusing specifically on shifts in customer behavior and the impact of fintech innovations. The review explores the evolution of banking services from traditional to digital-first models and analyzes how customer preferences for speed, convenience, and personalization are reshaping service delivery. Furthermore, it examines the disruptive and collaborative roles of fintech models, such as e-wallets, peer-to-peer lending, and open banking, on the established banking ecosystem. Key challenges for traditional banks, including issues of cybersecurity, regulatory compliance, and digital financial inclusion, are also discussed. The review concludes by highlighting the strategic imperative for banks to adopt an innovative and collaborative mindset, emphasizing that future success depends on their ability to integrate digital capabilities and adapt to a dynamic, customer-centric landscape.